Theoretical study of N2O2 interaction with BaO(100) surface - Ferullo, Ricardo (2007)
In this work, the adsorption of the NO dimer on BaO(1 0 0) was studied using the density functional theory (DFT). N2O2 interacts with the surface mainly in three different ways. In the more favoured orientation it adsorbs N-down forming a partially covalent bond with the surface with a charge electron delocalization over the adsorbate. In Tilted and O-down orientations, the dimer interacts in an electrostatic way with the surface Ba cations. The latter bonding modes are possible because an almost full electronic transfer from BaO to N2O2 takes place, producing the N2 species. In all these cases, the N–N distance of dimer decreases substantially due to the occupation of its 2b1 orbital, which has a very strong N–N bonding character. The results suggest that the formation of NO dimer should take place only at relatively high NO coverages.